Diet Supplementation With Pomegranate Peel Extract Altered Odorants Emission From Fresh and Incubated Calves' Feces - Varma, Vempalli S.; Shabtay, Ariel; Yishay, Moran; Mizrahi, Itzhak; Shterzer, Naama; Freilich, Shiri; Medina, Shlomit; Agmon, Rotem; Laor, Yael (Frontiers in Sustainable Food Systems, 2018)
Emissions of odorous volatile organic compounds (VOCs) from livestock manure are of increasing environmental concern. Recent approaches in cattle nutrition and health make use of Mediterranean fruit byproducts, such as concentrated pomegranate peel extract (CPE) that carry antioxidant activities, which in turn may alter manure properties. This study explored the effect of CPE on odorants emission from beef calves feces. Fourteen calves were randomly assigned to control (n=7) and pomegranate (n=7) treatments. The latter was supplemented with 4% CPE in milk until weaning at the age of 60d. Following weaning, 4% CPE was added to calves ration, on dry matter basis. The control treatment received only milk or solid feed, respectively. Fresh feces of the four treatments (control/pomegranate; before/after weaning) were sampled twice, 2-3w before and 4-5w after weaning, and then incubated (28°C) for 0, 7, 14, and 30d. Sub-samples were placed in a flux chamber (37°C) and VOCs collected on thermal desorption (TD) tubes followed by TD-GC-MS analysis. In all treatments, flux quantities followed the general order of volatile fatty acids (VFAs) > alcohols > phenolic & aromatic > sulfuric > esters > aldehydes. Total VOCs, especially VFA fluxes, peaked on day 7 in correspondence with pH dynamics. The fractional contribution of alcohols, phenolic & aromatic and sulfuric VOCs generally increased during incubation. After weaning, short-chain VFAs flux was 5.2 times higher and the pH was 1.26 units lower in the pomegranate treatment (average on days 7&14), suggesting increased fermentation due to possible effect of CPE on gastrointestinal microflora. An automated ribosomal intergenic spacer analysis of fresh and incubated fecal DNA confirmed association between microbial fingerprinting and short chain VFAs, phenolic and sulfuric VOCs. Odorants emission after weaning, expressed as odor activity values, was 2 times higher in the pomegranate treatment (average on days 7&14) and generally dominated by VFAs, while in other treatments the contribution of phenolic and sulfuric odors increased as incubation proceeded. In conclusion, diet supplementation with CPE may be adopted with the purpose of increasing calves health and production, but it may alter odor characteristics of feces and increase feedlot nuisance if not managed properly.